Ken Dark and Jan Kostenec, Hagia Sophia in Context. An Archaeological Re-examination of the Cathedral of Byzantine Constantinople. - Cormack, Robin (Journal of Greek Archaeology, 2022)
Ken Dark and Jan Kostenec, Hagia Sophia in Context. An Archaeological Re-examination of the Cathedral of Byzantine Constantinople. pp. 152, with ills. Oxford: Oxbow, 2019. ISBN 978-1-78925-030-5, hardcover £55.